The determination of optimal initial tension in rat coronary artery using wire myography - Ping, N-N; Cao, L; Xiao, X; Li, S; Cao, Y-X (Physiological research, 2014)
The aim of the present study was to determine the optimal initial tension, i.e. initial stretch for rat coronary artery when using the multi-wire myograph system. We used the normalization procedure to mimic physiological conditions and to stretch the coronary arterial segments to normalized internal circumference (IC(1)). It is determined the internal circumference when the vessel relaxed under a transmural pressure of 100 mm Hg (IC(100)), and the IC(1) is calculated by multiplying the IC(100) by a factor k. The impact of different factor k on the initial stretch and agonist-induced tension of coronary arteries were investigated. The results showed that the maximal agonist-induced tension was achieved at the factor k value of 0.90 and the initial stretch tension was given 1.16+/-0.04 mN/mm. The most appropriate factor k value was 0.90-0.95 and the most appropriate initial tension was 1.16-1.52 mN/mm. The equilibration time of the coronary artery segments should be at least 1.0 h. In the same optimal initial tension, the agonist-induced tension increased as equilibration time lengthened.
Keywords: koronární cévy; Coronary Vessels; Vasoconstriction; Bone Wires; krysa rodu Rattus; vazokonstrikce; Myography; Rats, Sprague-Dawley; Male; Animals; orgánové kultury - kultivační techniky; mužské pohlaví; myografie; potkani Sprague-Dawley; Organ Culture Techniques; zvířata; kostní dráty; Rats